2017
DOI: 10.3102/0162373717704303
|View full text |Cite
|
Sign up to set email alerts
|

Educational Effects of Banning Access to In-State Resident Tuition for Unauthorized Immigrant Students

Abstract: This research examines the effects of state laws banning access to in-state resident tuition for unauthorized immigrant students in the United States. These laws were implemented between 2005 and 2012. We evaluate the policy effects on (a) college enrollment, (b) school dropout rates of unauthorized immigrants, and (c) the enrollment of U.S. citizens in higher education. Multivariate triple-differences models are used. We find significant negative effects on the college attendance rates of unauthorized immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…I compare changes in the outcomes of interest between Hispanic undocumented students and a comparison group of U.S.-born Hispanics in those same counties. U.S.-born Hispanics are the most appropriate comparison group because they are likely to experience similar educational, economic, cultural, and social conditions compared with other racial/ethnic groups that could serve as comparison groups (Chin & Juhn, 2011;Flores, 2010;Villarraga-Orjuela & Kerr, 2017). I implement this design using the following linear probability model:…”
Section: Methodsmentioning
confidence: 99%
“…I compare changes in the outcomes of interest between Hispanic undocumented students and a comparison group of U.S.-born Hispanics in those same counties. U.S.-born Hispanics are the most appropriate comparison group because they are likely to experience similar educational, economic, cultural, and social conditions compared with other racial/ethnic groups that could serve as comparison groups (Chin & Juhn, 2011;Flores, 2010;Villarraga-Orjuela & Kerr, 2017). I implement this design using the following linear probability model:…”
Section: Methodsmentioning
confidence: 99%
“…ISRT also affects the timing of college enrollment and in 4 which institutions undocumented students choose to enroll (Darolia & Potochnick, 2015). Highlighting the power of ISRT for promoting undocumented student college enrollment is the corollary finding that states with ISRT bans saw significant reductions in undocumented student college enrollment (Villarraga-Orjuela & Kerr, 2017).…”
Section: In-state Resident Tuitionmentioning
confidence: 99%
“…ISRT also affects the timing of college enrollment and in which institutions undocumented students choose to enroll (Darolia & Potochnick, 2015). Underscoring the role of ISRT policies in making higher education more accessible for undocumented immigrants, a study of six states that banned ISRT (e.g., Arizona, Colorado, Georgia, Indiana, Montana, and Ohio) showed that ISRT bans reduced undocumented student enrollment (Villaraga‐Orjuela & Kerr, 2017). However, some studies have shown that the existence of ISRT alone does not necessarily increase college enrollment in states that enact ISRT, rather, that states with bans decrease undocumented student college enrollment (Bozick, Miller, & Kaneshiro, 2016).…”
Section: Supportive Policymentioning
confidence: 99%